2019
DOI: 10.1002/ps.5446
|View full text |Cite
|
Sign up to set email alerts
|

tau‐Fluvalinate and other pesticide residues in honey bees before overwintering

Abstract: BACKGROUND Pesticides have often been linked to honey bee colony losses, which occur mainly over winter. In this study, we investigated residues in nine colonies at a model agricultural research site during the period before wintering. Moreover, we applied the acaricide tau‐fluvalinate to the colonies via a strip formulation. The pesticide content was determined by UHPLC‐QqQ‐MS/MS in bees from brood comb initially collected in mid‐September immediately prior to the start of tau‐fluvalinate treatment and 30 lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
3
10
1
Order By: Relevance
“…However, the similar imidacloprid concentrations in females and cocoons may indicate a low metabolism level of imidacloprid. In the previous study, we detected only imidacloprid‐urea metabolites in honeybees, which we suggested to be the result of historical contamination by imidacloprid; in addition, the detection in webs with prey remnants is likely consistent with that suggestion, or the metabolite imidacloprid‐urea could arise from prey metabolization of imidacloprid.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…However, the similar imidacloprid concentrations in females and cocoons may indicate a low metabolism level of imidacloprid. In the previous study, we detected only imidacloprid‐urea metabolites in honeybees, which we suggested to be the result of historical contamination by imidacloprid; in addition, the detection in webs with prey remnants is likely consistent with that suggestion, or the metabolite imidacloprid‐urea could arise from prey metabolization of imidacloprid.…”
Section: Resultssupporting
confidence: 77%
“…Thus, these compounds likely originated from the prey. Previously, we also detected these compounds in honeybees in the same area . Here, we show that these plant growth regulators can be found, as in honeybees, in similar amounts to commonly used pesticides in spider matrices.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations